Pengaruh Penggunaan Model Two Stay Two Stray Berbantuan Media Video Youtube Terhadap Keterampilan Siswa Kelas X Dalam Menulis Teks Eskposisi Di SMAS Budisatrya Medan - Shaniya Meirisa; Khairil Ansari (Universitas Palangka Raya, 2024)
The aim of the research is to determine the superiority of students in writing persuasive texts This research is useful to determine the ability to write expository text before and after using the Two Stay Two Stray model assisted by YouTube video media and to determine the effect of using the Two Stay Two Stray model assisted by YouTube video media on the skills of writing expository text in Class X SMAS Budisatrya students. This research applies an experimental method with a one group pre-test post-test design. The population in this research was 68 class X SMAS Budisatrya students and a sample of 32 class X IPS 2 students. Data analysis techniques include normality testing and hypothesis testing. The results of the research show that the average value of students' skills before using the Two Stay Two Stray model assisted by YouTube video media is 39.69, which is classified as very poor, while the average value of students' skills after using the Two Stay Two Stray model assisted by YouTube video media is 78.75 is classified as good. Based on the t test, the value obtained at the significant level α = 0.05 obtained the t table value of 9.53 and the result of t = 2.040. So, tcount>ttable is 9.53>2.040 so h0 is rejected and ha is accepted. Thus, the results of this research are: 1) the ability to write expository text before using the Two Stay Two Stray model assisted by YouTube video media is classified as very poor. 2) the ability to write expository text after using the Two Stay Two Stray model assisted by YouTube video media is in the good category. 3) There is a significant influence from the use of the Two Stay Two Stray model assisted by YouTube video media on expository text writing skills in Class X SMAS Budisatrya students.